THE USE OF TEAM PRODUCT TO IMPROVE STUDENTS’ CREATIVITY IN WRITING AT SMKN 2 LINGSAR - Dian Novia Isroyana; Heri Hidayatullah; Bq Zuhrotun Nafisah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
This research was about the use of team product to improve students’ creativity in writing at SMKN 2 Lingsar in academic year 2018/2019. This research used Classroom Action Research. The data in this research was taken from the mean scores of students’ achievement and the score percentages. The subject of this research was X grade students of SMKN 2 Lingsar, which consisted of 19 students. This research was conducted in two cycles. The instruments of this research were test, questionnaire, and observation sheet. The mean score of students’ creativity in writing in the first cycle was 52 with percentage (40%) of the students still low creativity than the researcher done the second cycle. The mean score and percentage of students’ achievements was higher than criteria of success (70). The result indicated the mean score of the students’ creativity in writing was 77, 1 with percentage (84, 21%) for students who passed the minimum criteria of success (KKM). It was indicated that the use of team product method can improve students’ creativity in writing.